Effect of Theory of Planned Behaviour-Based Structured Education on Knowledge and Interdialytic Weight Gain Among Patients with Chronic Kidney Disease - Diah Setiani; Rosdiana Rosdiana; Rivan Firdaus; Indah Nur Imamah; Hesti Prawita Widiastuti (Borneo Scientific Publishing, 2026)
Globally, CKD and ESRD continue to increase substantially with the majority receiving dialysis treatment, involves an irreversible decline in kidney function so that continuous dialysis is carried out for survival. The success of haemodialysis therapy is highly dependent on patient adherence, especially in controlling interdialytic weight gain (IDWG). Knowledge and behavior patient are required in the control of IDWG. One of the health education models is used to increase knowledge so that it has an impact on health-related behaviour change, namely Planned Behaviour Theory (TPB). This study aimed to determine the effect of Theory Planned Behaviour-based structured education on knowledge of fluid restriction and IDWG reduction in CKD patients on haemodialysis. The research employed a quantitative method design using an quasi-experimental pretest-posttest with a control group design. The population of all patients analyzed at the Inche Abdoel Moeis Regional General Hospital, Samarinda, amounted to 60 respondents, sample technique used purposive sampling (according to the inclusion criteria), each group amounted to 30 respondents (with intervention and control groups) The intervention group received structured education based on the TPB and fluid evaluation monitoring with discussion forums. Intervention groups are given with a frequency of education 2x a week, the duration education was 30 minutes and then total implementation was 4 weeks, used instruments consisting of the SOP for Providing TPB-Based Education, IDWG observation sheets, and questionnaires (the questionnaire validity and reliability Cronbach’s Alpha is 0.760). And statistical tests using paired t-tests and independent t-tests. The results of the hypothesis test in the intervention group with the Paired T-test obtained a p value of 0.000<0.05. Meanwhile, in the control group, the p-value was 0.053>0.05. There were significant differences between the intervention and control groups, so it was concluded that there was an effect of TPB-based structured education on knowledge of fluid restriction and IDWG reduction in CKD patients on haemodialysis.